An alternative method for the separation and analysis of acidic biomarkers from crude oil samples. (December 2022) - Costa de Sousa, Alek André; da Silva Sousa, Edymilaís; Rodrigues de Sousa Junior, Gustavo; Carbonezi, Carlos Alberto; Durante Spigolon, Andre Luiz; Brito, Ailton Silva; Gonçalo de Lima, Sidney
Abstract: This study aimed to develop and/or optimize a method of separation and analysis of neutral and acidic constituents from oil samples from Brazilian sedimentary basins and make a broad characterization of these samples through the respective molecular fossils. Three oil samples (A, B and C) of different origins and biodegradation were analyzed in this work. The neutral fractions were subjected to classic separation processes using gradient elution and analyzed by gas chromatography–mass spectrometry (GC–MS). The acidic fraction was isolated using KOH modified silica as stationary, adapted in SPE, and analyzed by GC–MS as silylated derivatives. The molecular parameters for B oil suggest a marine evaporitic depositional environment, with less continental influence, low siliciclastic sediments input, low oxygenation, hypersaline, stratified water column, and persistent photic zone euxinic. For the A and C oils, the parameters indicate a significant similarity between the samples, differing essentially only in the absence of acyclic n-alkanes and isoprenoids because of different stages of biodegradation. The presence of TPP and β-carotane in samples A and C allows us to classify them as mixed origin, with characteristics of lacustrine freshwater and saline depositional environments. Biomarkers associated with dinoflagellates of marine origin in the saturated fraction (dinosteranes) and the aromatic fraction (triaromatic dinosteranes) were detected in all three samples and suggest dinoflagellates were important primary producers during deposition time. 25-Norhopanes were detected only at low concentrations, and biomarker-based geochemical parameters indicate the biodegradation did not change the distribution of steranes and hopanes. The 25-Norhopanoic acids detection also agree with the detection of 25-norhopanes in the A and C oils, supports the same order of biodegradation, C > A ≫ B. The low abundance of tricyclic terpanoic acids in oil B acidic fraction agrees with the low abundance of tricyclic terpanes into the corresponding neutral fraction. Unlike hopanes, hopanoic acids distribution shows the ββ-isomers, biologically and thermally less stable configuration. Especially in oil B, series of 3-carboxysteranes, 3-carboxymethylsteranes were observed. In summary, acidic fractions data from three samples indicate that acidic biomarkers provide parallel information and complementary to that obtained from the hydrocarbon biomarkers. The extraction methods, derivatization and analysis of carboxylic acids from oil samples proved to be efficient, leading to quantitative recoveries and good yields. Highlights: Hopanoic acids in Meso-Cenozoic Brazilian marginal basins oils. Separation and analysis method of acidic biomarkers from crude oil samples. Pentacyclic terpanoic acids and 3-carboxyalkylesteranes. Depositional paleoenvironment. Biomarkers associated to dinoflagellates.